Lysine-specific demethylase 1 (LSD1)-mediated epigenetic modification of immunogenicity and immunomodulatory effects in breast cancers - Lee, Dong Yeul (2024)
Tumor evolution to evade immune surveillance is a hallmark of carcinogenesis, and the modulation of tumor immunogenicity has been a challenge to present therapeutic responses in immunotherapies alone for numerous cancers. By altering the cell phenotype and reshaping the tumor microenvironment, epigenetic modifications enable tumor cells to overcome immune surveillance as a mechanism of cancer progression and immunotherapy resistance. Demethylase enzymatic activity of lysine-specific demethylase 1 (LSD1), a histone demethylase first identified in 2004, plays a pivotal role in the vast cellular processes of cancer. While FDA-approved indications for epigenetic therapies are limited to hematological malignancies, it is imperative to understand how epigenetic machinery can be targeted to prime immunotherapy responses in breast cancers. In this review, we discuss the potential roles of epigenetics and demethylating agent LSD1 as a potent new cancer management strategy to combat the current challenges of breast cancers, which have presented modest efficacy to immune checkpoint inhibitors till date. Additionally, we describe the combined use of LSD1-specific inhibitors and immune checkpoint inhibitors in existing breast cancer preclinical and clinical trials that elicits a robust immune response and benefit. Overall, the promising results observed in LSD1-targeting therapies signify the central role of epigenetics as a potential novel strategy to overcome resistance commonly seen in immunotherapies.